Islamic Trade Finance : An Opportunity for Malaysia - World Bank (World Bank, Kuala Lumpur, 2021)
Islamic trade finance (ITF) offers a meaningful opportunity for Malaysia. ITF can play a substantial role to support trade, foster growth, and accelerate post-pandemic recovery. In addition to its impact on the domestic economy, enhancing ITF can bring benefits to other Organization of Islamic Countries (OIC)-member countries and for the global Islamic finance industry in which Malaysia is an established leader. This report explores the ITF opportunity by considering: (1) the current state of global trade finance and of ITF; (2) institutions and instruments active in providing ITF; (3) key challenges ahead in expanding ITF; and (4) opportunities for expanding ITF in Malaysia. The report includes (5) a set of recommendations for stakeholders in Malaysia and beyond to avail of the opportunity that ITF offers. While the recommendations are focused on Malaysia, they may also have relevance for other developing economies where Islamic finance is relevant. The report argues that key strides have already been made in Malaysia and globally to establish ITF concepts, products, and structures. The relative under-utilization of ITF is due to challenges related to awareness, promotion, scale, and harmonization. Addressing these challenges, through a set of recommendations, can foster ongoing growth of ITF in service of Malaysia’s development objectives.